Fatty Acids Change the Conformation of Uncoupling Protein 1 (UCP1) - Divakaruni, Ajit S. (American Society for Biochemistry and Molecular Biology, 2012)
UCP1 catalyzes proton leak across the mitochondrial inner membrane to disengage substrate oxidation from ATP production. It is well established that UCP1 is activated by fatty acids and inhibited by purine nucleotides, but precisely how this regulation occurs remains unsettled. Although fatty acids can competitively overcome nucleotide inhibition in functional assays, fatty acids have little effect on purine nucleotide binding. Here, we present the first demonstration that fatty acids induce a conformational change in UCP1. Palmitate dramatically changed the binding kinetics of 2′/3′-O-(N-methylanthraniloyl)-GDP, a fluorescently labeled nucleotide analog, for UCP1. Furthermore, palmitate accelerated the rate of enzymatic proteolysis of UCP1. The altered kinetics of both processes indicate that fatty acids change the conformation of UCP1, reconciling the apparent discrepancy between existing functional and ligand binding data. Our results provide a framework for how fatty acids and nucleotides compete to regulate the activity of UCP1.